Indian clinical practice consensus guidelines for the management of locoregional laryngeal cancer - Update 2023 - Manish Singhal; K. Govind Babu; HS Darling; Pankaj Chaturvedi; Moni Kuriakose; Praveen Birur; Ashish Kaushal; Abhishek Mahajan; Munish Gairola; Sumit Goyal; Vijay M Patil; Vanita Noronha; et al. (Cancer Research, Statistics, and Treatment)
Laryngeal cancer typically presents at a nonmetastatic stage, and the majority of patients are treated with curative intent. Due to the functional and cosmetic morbidities associated with surgical approaches, nonsurgical modalities are increasingly favored. This update to the guidelines emphasizes a multidisciplinary approach tailored to the Indian healthcare context, enhancing treatment strategies and optimizing patient outcomes. Key recommendations include the use of concurrent chemoradiotherapy and induction chemotherapy regimens, with a focus on organ preservation whenever feasible.